2018
DOI: 10.2147/dddt.s153898
|View full text |Cite
|
Sign up to set email alerts
|

Islet protection and amelioration of type 2 diabetes mellitus by treatment with quercetin from the flowers of <em>Edgeworthia gardneri</em>

Abstract: Background and purposeThe traditional Chinese medicine – the flower of Edgeworthia gardneri – is reported as an effective therapeutic for type 2 diabetes mellitus (T2DM). Nevertheless, most constituents of the flowers of E. gardneri have not yet been studied. This study was conducted to investigate the effect of quercetin extracted from the flowers of E. gardneri on islet protection and amelioration in T2DM and explore its mechanism.MethodQuercetin was extracted from the flowers of E. gardneri and verified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Quercetin is a natural flavonoid that is widely distributed in fruits and vegetables. [ 8 ] It has antioxidant, anti‐inflammatory, antitumor, and antimutation physiological functions. [ 9–12 ] Epidemiologic studies have suggested that increasing quercetin intake can reduce the risk of certain chronic diseases, such as cardiovascular disease, osteoporosis, and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin is a natural flavonoid that is widely distributed in fruits and vegetables. [ 8 ] It has antioxidant, anti‐inflammatory, antitumor, and antimutation physiological functions. [ 9–12 ] Epidemiologic studies have suggested that increasing quercetin intake can reduce the risk of certain chronic diseases, such as cardiovascular disease, osteoporosis, and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds have received much attention due to their structural diversity, richness, strong pharmacological activity, and safety [38]. Numerous studies have reported the biological effects of quercetin, and its potential benefits as an anti-cancer, anti-oxidative, and anti-inflammatory agent, especially in the treatment of type 2 diabetes mellitus [39][40][41][42]. Quercetin can improve the symptoms and eliminate the complications of diabetes [38,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…We and others reported that the polyphenol quercetin enhanced the insulin secreting activity of pancreatic b-cells and protected this key function from environmental insults which is crucial for appropriate control of glucose homeostasis [7,16,17,22,23]. Mechanistically, quercetin facilitated depolarization-induced L-type Ca 2+ currents and increased intracellular Ca 2+ concentration which is essential to trigger exocytosis [24].…”
Section: Introductionmentioning
confidence: 95%
“…Importantly, quercetin also enhanced glucose-mediated ERK1/2 activation which contributes to its insulin secreting action. Indeed, inhibition of MAPK kinases (MAPKK) proteins, the upstream activators of ERK1/2, decreased the stimulatory effect of quercetin on glucose-induced insulin secretion [16,22]. Besides polyphenols, we recently reported that a few of their metabolites also exert pharmacological action in pancreatic b-cells.…”
Section: Introductionmentioning
confidence: 99%